Parallel iterative methods for solving systems of generalized mixed equilibrium problems in reflexive Banach spaces. (3rd April 2017) - Tuyen, Truong Minh
Abstract : The purpose of this paper is to introduce three parallel iterative methods which use techniques of Bregman distances, Bregman projections, Bregman strongly nonexpansive operators and hybrid or shrinking projection methods to solve systems of generalized mixed equilibrium problems in a real reflexive Banach space.